Congratulations! - Tretyak, A. (Land Management, Cadastre and Land Monitoring, 2018)
January 19, 2018 marks the 80th anniversary of Alexander Yakovlevich Panchuk, a well-known in Ukraine and abroad, as an authoritative specialist in land management, land valuation, cadastre, problems of rational use and protection of land resources. In different years - a member of the college of the State Committee for Land Resources, scientific and technical councils of the Institute of Land Management of the UAAS, the State Committee for Land Resources, the National Agrarian University, a member of the Presidium of the Union of Land Surveyors of Ukraine.